Histone Variant H2A.Z and RNA Polymerase II Transcription Elongation - Santisteban, Maria Soledad (American Society for Microbiology, 2011)

(untitled)
Nucleosomes containing histone variant H2A.Z (Htz1) serve to poise quiescent genes for activation and transcriptional initiation. However, little is known about their role in transcription elongation. Here we show that dominant mutations in the elongation genes SPT5 and SPT16 suppress the hypersensitivity of htz1Δ strains to drugs that inhibit elongation, indicating that Htz1 functions at the level of transcription elongation. Direct kinetic measurements of RNA polymerase II (Pol II) movement across the 9.5-kb GAL10p-VPS13 gene revealed that the elongation rate of polymerase is 24% slower in the absence of Htz1. We provide evidence for two nonexclusive mechanisms. First, we observed that both the phospho-Ser2 levels in the elongating isoform of Pol II and the loading of Spt5 and Elongator over the GAL1 open reading frame (ORF) depend on Htz1. Second, in the absence of Htz1, the density of nucleosome occupancy is increased over the GAL10p-VPS13 ORF and the chromatin is refractory to remodeling during active transcription. These results establish a mechanistic role for Htz1 in transcription elongation and suggest that Htz1-containing nucleosomes facilitate Pol II passage by affecting the correct assembly and modification status of Pol II elongation complexes and by favoring efficient nucleosome remodeling over the gene.